2009
DOI: 10.1080/17421770903114711
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Convergence in Income Per Capita and Income Inequality in the Regions of the EU

Abstract: The neoclassical growth model predicts that there will be both a reduction of income per capita disparities over time and long-term convergence in income inequality levels. This paper examines whether this holds true for the EU using data from the European Community Household Panel for 102 regions over the period 1995–2000. The analysis is conducted using cross-sectional and panel data growth models with spatial interaction effects. The results reveal the presence of a conditional convergence in income per cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 58 publications
0
51
0
5
Order By: Relevance
“…There are now numerous studies that have estimated absolute and conditional beta convergence for the regions, with the more recent ones mainly concentrating on conditional beta convergence. See, for example, Barro and Sala-i- Martin (1991Martin ( , 2004, Armstrong (1995), Evans and Karras (1996), Rey and Montouri (1997), Garofalo and Yamarik (2002), Badinger et al (2004), Egger et al (2006), Benos and Karagiannis (2008), Esposti and Bussoletti (2008), and Tselios (2009). See also the survey of Martin and Sunley (1998).…”
Section: Regional Convergence and The Aggregate Production Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are now numerous studies that have estimated absolute and conditional beta convergence for the regions, with the more recent ones mainly concentrating on conditional beta convergence. See, for example, Barro and Sala-i- Martin (1991Martin ( , 2004, Armstrong (1995), Evans and Karras (1996), Rey and Montouri (1997), Garofalo and Yamarik (2002), Badinger et al (2004), Egger et al (2006), Benos and Karagiannis (2008), Esposti and Bussoletti (2008), and Tselios (2009). See also the survey of Martin and Sunley (1998).…”
Section: Regional Convergence and The Aggregate Production Functionmentioning
confidence: 99%
“…See also the surveys on agglomeration economies by Rosenthal andStrange (2004, 2006) and the World Bank (2009, chapter 4). The rate of regional productivity convergence is considered by Armstrong (1995), Barro andSala-i-Martin (1991, 2004, especially chapter 11), Eckey et al (2007), Maier andTrippl (2009), andTselios (2009). The aggregate production function is central to all these applied studies and is used widely in theoretical spatial modeling.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies added a further dimension to classical convergence studies by including the questions of income distribution and the growth rates of income (Tselios, V. 2009;Amarante, V. 2014;Castells-Quintana, D. and Royuela, V. 2014). For example, as Tselios (2009) suggested, there is a convergence not just in the growth rate of income, but also in growth rates of income inequalities.…”
Section: New Approaches To Unequal Development and Growthmentioning
confidence: 99%
“…Some studies (see [87]) suggested the presence of a conditional convergence in income per capita and that of an unconditional convergence in income inequality in many regions of the EU, while other studies indicated that the weak or even the lack of economic convergence is not matched by a similar absence of social convergence, as the welfare levels have converged significantly across European regions, although the regions with high social welfare levels may remain advantaged in welfare terms, while the low social welfare regions may continue to lag behind [109].…”
Section: In the European Union An Index Of Competitiveness Of The Rementioning
confidence: 99%
“…The main indicators used to analyze real convergence refer to the differences in GDP per capita at purchasing power parity and in income per capita, differences in labor productivity, and the price level (e.g., [87][88][89][90]). The literature highlights several indicators that can be used to assess the real convergence process, from broader indicators (GDP growth rate, GDP per capita, the ratio of exports to GDP, the intensity of foreign investment, stock market capitalization, unemployment rates, labor costs and R&D expenditures, etc.)…”
Section: In the European Union An Index Of Competitiveness Of The Rementioning
confidence: 99%